PENGARUH CHARACTER, CAPACITY, CAPITAL, CONDITION DAN COLLATERAL TERHADAP KEPUTUSAN PEMBERIAN PEMBIAYAAN PADA PT BANK SUMUT DIVISI USAHA SYARIAH - Rahima Kumala; S Sugianto; Muhammad Ridwan (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2021)
This study aims to determine how much influence the character, capacity, capital, condition and collateral have on the decision to provide financing at PT. SUMUT Bank Syariah Business Division. The research approach used is a quantitative research approach. The sample in this study were employees of PT Bank SUMUT Syariah Business Division who are domiciled in Syariah Branch Offices and Syariah Branch Offices related to the process of providing financing and the number of samples taken was 82 people. The instrument used to obtain data was a questionnaire using a Likert scale. This study uses multiple linear analysis. Supported by the validity and reliability tests, the classical assumption test, the t test and the f test using the SPSS version 22 software. The results of this study indicate that simultaneously, the variable character, capacity, capital, condition and collateral have a significant effect on the decision to provide financing at PT. Bank SUMUT Syariah Business Division and partial test results show that all independent variables, namely character, capacity, capital, condition and collateral have a significant effect on the decision to provide financing at PT Bank Sumut the Syariah Business Division.